The Effect of Early Enteral Immunonutrition to Inflammatory Response for Intensive Care Patients - Celik, Fatma; Edipoglu, Ipek Saadet (Galenos Yayincilik, 2019)
Objective: Early enteral immunonutrition affects cytokine-dependent stress response, providing an optimal inflammatory and immune response in the dynamic process of SIRS through sepsis. In our study, we examined the inflammatory response of standard and glutamine products in the early and late nutrition regimen. Materials and Methods: Forty patients aged between 30 and 60 who needed ventilation support were randomly divided into 4 groups, namely standard early enteral (SE), standard late enteral (SG), early enteral immunonutrition (IE) and late enteral immunonutrition (IG). In early enteral nutrition groups, nutrition started within the first 24 hours of treatment and after 72 hours in the late groups. Prealbumin, albumin, CRP, IL-6, IL-10, APACHE II and mortality were calculated. Results: There was no difference in terms of demographics. We found a decrease in the prealbumin level in the SE group (p<0.05). There was a decrease in CRP levels in the IE and IG groups compared to SG group. There was an increase in SE group at 5th and 7th days (p<0.05). In terms of IL-6 levels, we found a decrease in the IE, SE, IG groups compared to SG group. In the IE group, IL-6 level was decreased compared to IG and SE groups at the 7th day. IL-10 level in the IG group increased at 5th and 7th days. APACHE II scores at 5th day were higher in the IG group compared to SG group. There was no difference in terms of mortality. Conclusion: It was concluded that glutamine-rich early enteral immunonutrition efficiently suppressed the systemic inflammatory response without affecting mortality and biochemical parameters.
Keywords: Glutamine; early enteral nutrition; immunonutrition